Pelatihan Pengolahan Minyak Jelantah Menjadi Sabun Cuci Batangan dan Lilin Aromaterapi - Husnayaen, Husnayaen; Rahmawati, Suci; Arini, Dwi Puspa; Chonnaniyah, Chonnaniyah; Lestari, Windy; Anhar, Alfian (Bumi Lestari; Vol 23 No 1 (2023)DO - 10.24843/blje.2023.v23.i01.p01, 2022)
Cooking oil is one of the primary ingredients that must be available for the household needs of Indonesians. Population growth, industrial development, restaurants, and fast-food restaurants cause the use of cooking oil to increase. The increase in the use of cooking oil will cause an increase in frying waste. Waste cooking oil that is not managed properly will cause pollution. Lack of public awareness of the dangers of waste cooking oil to the environment so there is a need for guidance to the community regarding the dangers of disposing of used cooking oil waste into the environment and providing solutions for the use of waste cooking oil in new products that have economic value. Therefore, as a community service from the Institute of Science and Technology of Nahdlatul Ulama Bali (ISTNUBA), we try to invite the community in Banjar Anyar Village, Kediri, Tabanan Regency, Bali to be able to participate in training on processing waste cooking oil into bar washing soap and aromatherapy candles. The method is counseling and distribution of brochures about the dangers and benefits of waste cooking oil. This training activity is expected to increase public knowledge and awareness of managing waste cooking oil and can open up entrepreneurial opportunities, create jobs and improve the living standards of the surrounding community.